Ischemic preconditioning prevents endothelial injury and systemic neutrophil activation during ischemia-reperfusion in humans in vivo. - Kharbanda, R; Peters, M; Walton, B; Kattenhorn, M; Mullen, M; Klein, N; Vallance, P; Deanfield, J; MacAllister, R (2001)
BACKGROUND: Endothelial dysfunction leading to neutrophil infiltration of tissues has been implicated in tissue injury caused by ischemia-reperfusion (IR). Tissue injury during IR can be reduced by prior ischemic preconditioning (IPC). In humans, it is unclear whether endothelial dysfunction occurs during IR or whether IPC offers protection against endothelial dysfunction and inflammatory cell activation. We studied the effects of experimental IR on endothelial and neutrophil function in the human forearm in vivo and examined the protection afforded by IPC. METHOD AND RESULTS: The forearm was made ischemic for 20 minutes by inflating a blood pressure cuff to 200 mm Hg. We assessed endothelial function of conduit (radial artery flow-mediated dilation) and resistance vessels (blood flow responses to intra-arterial infusion of the endothelium-dependent dilator acetylcholine) in healthy volunteers before and after IR. IR reduced flow-mediated dilation of the radial artery at 15 minutes of reperfusion (7.7+/-1.5% to 3.5+/-0.9%) and the dilator response of resistance vessels to acetylcholine at 15, 30, and 60 minutes of reperfusion. IR did not reduce the dilator response of the radial artery to glyceryltrinitrate and only caused a small reduction of glyceryltrinitrate-induced dilation of resistance vessels at 60 minutes of reperfusion. IR caused an increase in neutrophil CD11b expression and platelet-neutrophil complexes in the circulating blood. IPC (three 5-minute episodes of ischemia) before IR prevented endothelial dysfunction and neutrophil activation. CONCLUSIONS: A clinically relevant period of ischemia-reperfusion causes profound and sustained endothelial dysfunction and systemic neutrophil activation. IPC attenuates both of these effects in humans.